2013
DOI: 10.5558/tfc2013-064
|View full text |Cite
|
Sign up to set email alerts
|

Do partial cuts create forest complexity? A new approach to measuring the complexity of forest patterns using photographs and the mean information gain

Abstract: Forest management generally simplifies forest structure and composition with some negative impacts in terms of biodiversity and resilience. Thus, maintaining structural complexity is increasingly cited as an objective of sustainable forest management. Different initiatives have been proposed to use partial cuts to increase the complexity of forests. Using “the length of description” of forest patterns as a novel measure of complexity in forests, the effects of two intensities of partial cuts were compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In order to imitate complex structures of primary forests, we first need to make their characteristic structures measurable and reproducible. Despite approaches to quantify complexity without 3D measurements, such as the structural complexity index (SCI) [22], the mean information gain index (MIG) [23], or the arc-chord ratio (ACR) rugosity index [24], terrestrial laser scanning (TLS) has shown to be an efficient and effective method allowing for an accurate and precise assessment of three-dimensional forest structure [25][26][27]. In combination with methods for quantifying complexity, such as fractal analysis [28], the structural complexity of forests can be assessed mathematically.…”
Section: Introductionmentioning
confidence: 99%
“…In order to imitate complex structures of primary forests, we first need to make their characteristic structures measurable and reproducible. Despite approaches to quantify complexity without 3D measurements, such as the structural complexity index (SCI) [22], the mean information gain index (MIG) [23], or the arc-chord ratio (ACR) rugosity index [24], terrestrial laser scanning (TLS) has shown to be an efficient and effective method allowing for an accurate and precise assessment of three-dimensional forest structure [25][26][27]. In combination with methods for quantifying complexity, such as fractal analysis [28], the structural complexity of forests can be assessed mathematically.…”
Section: Introductionmentioning
confidence: 99%